Academies of sciences and the scientific enterprise in the Islamic world and the west: a comparative study with reference to selected oic and western countries / Moneef Rafe’ Zou’bi - Zou’bi, Moneef Rafe (2012)

(untitled)
This Thesis is an interdisciplinary study of the academies of sciences and the scientific enterprise in the Islamic world and the West. It analyses the genesis, roles, functions and activities of academies of sciences over time and across civilisations, as well as contemporaneously. As there is a close nexus between academies of sciences and the milieus within which they flourish, the Thesis goes beyond existing literature and proposes an alternative chronology of the rise and decline of science in the Islamic civilisation and the ascendance of science in Europe. This is considered a perquisite to a better understanding of the current weakness of the scientific enterprise in the Islamic world and the relative absence of science culture within, compared to Europe and the West. Academies of sciences are organisations that have a long history. For many, they are shrouded in mystery. Their institutional characteristics, roles, functions and activities –although plausibly documented- are not well known. To address this, the institutional traits of some academies of sciences are investigated by means of an in-depth review of published literature, earlier studies and interviews. In order to make a bona fide contribution to promoting their role as indispensable pillars of science, technology and innovation (STI) systems, particularly in OIC countries, the Thesis streamlines the activities of academies of sciences into politics-oriented and policies-based components. The former include the provision of science-based advice, interaction with governments and parliaments, science diplomacy and international networking while the latter include science education and the promotion of scientific research, with the issue of women in science discussed under a separate heading. The comparative study chapter looks at 15 academies of sciences from around the world and includes a critique of the statutes of the model academy of sciences as adopted by the InterAcademy Panel (IAP). This may help to propagate best practices v within existing academies of sciences, and may prompt further work in adopting and adapting the model to individual country requirements in the future. The main findings of the study reveal that although historically their paths of science have crossed, there is today a wide gap in science, and the institutionalisation thereof, between the Islamic world and the West. Despite many top-down initiatives in science in the Islamic world, the tool of S&T as the platform for development is prized only by some scientists and, at best, a few political and community leaders. Lack of political patronage and support of science, despite a legacy of creativity and innovation, is a major cause of the poor output of the STI system in the Islamic world but it is not the only quandary. The lack of a culture of science manifested by the existence of around 26 academies of sciences in the 57 OIC-member countries is another. Moreover, most such academies are new, operate on shoestring budgets, and undertake a limited number of activities. None has thus far captured the spirit that prevailed around their ancient predecessors; however, some are trying to emulate the success of their counter-parts in the West